Prevalence of GSTM1*0 and CYP1A1*2A (rs4646903) variants in the central Peruvian coastal population: Pilot Study of predictive genetic biomarkers for 4P medicine - Alvarado, Angel T. (2025)
The CYP1A1 isoenzyme is responsible for the biotransformation of procarcinogens, such as Benzo(a)pyrene, into reactive metabolites. Meanwhile, GSTM1 facilitates the detoxification of these metabolites by conjugating them with glutathione. The presence of the CYP1A1*2A genetic variant intensifies the production of these reactive metabolites, and the deletion of the GSTM1 gene (GSTM1*0) impairs their detoxification. This enzymatic imbalance leads to the formation of DNA adducts, which are known to contribute to cancer and other diseases. Given the importance of studying these genes within the framework of 4P medicine (predictive, preventive, personalized, and participatory), the primary objective of this study was to investigate the prevalence of GSTM1*0 and CYP1A1*2A in the central Peruvian coastal Population as genetic biomarkers. The study included 131 individual residents of the Peruvian towns of Ica and Lima. The results showed a frequency of 0.47 for GSTM1*0 and an allele frequency of 0.68 for CYP1A1*2A. The genotype frequencies of CYP1A1*2A were 6% *1A/*1A, 53% *1A/*2A, and 41% *2A/*2A. Notably, the population sample is not in the Hardy-Weinberg equilibrium (χ2 = 5.324) for CYP1A1. The reported frequencies of GSTM1*0 and CYP1A1*2A in this study differ from those previously documented for other Latin American and tricontinental populations, potentially reflecting the unique natural evolution and genetic admixture of the Peruvian population. The high prevalence of GSTM1*0 and CYP1A1*2A identified in populations from Ica and Lima suggests a potentially elevated risk of exposure to procarcinogens such as polycyclic aromatic hydrocarbons (PAHs). This finding underscores the need for further research on a larger scale to validate and expand upon these results.